(untitled) (Bangladesh Critical Care Journal, 2023)
Methemoglobinemia is a potentially fatal condition at a level of more than 70%. It occurs when the ferrous iron in Haemoglobin is oxidized to ferric iron, forming methemoglobin (MetHb), causing decreased capability of hemoglobin to bind and deliver oxygen to tissues. Methemoglobinemia has been linked to a wide array of substances, including fungicides and industrial chemicals. We describe a patient who developed a high MetHb level of 70.7%, after deliberately consuming a fungicide, namely Mancozeb. The "oxygen saturation gap" is the difference between the calculated oxygen saturation from a standard blood gas machine and the reading from a pulse oximeter. If it is greater than 5%, the patient’s hemoglobin may be abnormal, representing carbon monoxide poisoning, methemoglobinemia, or sulfhemoglobinemia. Disproportionate cyanosis not responding to supplemental oxygen, chocolate brown blood, and saturation gap of >5% raised the suspicion of methemoglobinemia secondary to ingestion of fungicide. An alternative approach to treatment including intravenous ascorbic acid, NAC, and multiple blood transfusions was given due to the unavailability of methylene blue. A high index of suspicion, early recognition, and an alternative approach to management resulted in a favorable outcome. Bangladesh Crit Care J March 2023; 11 (1): 46-50